Jewish meaning in a world of choice : studies in tradition and modernity - Ellenson, David Harry, 1947- (JPS scholar of distinction series., 2014)
"Internationally recognized scholar David Ellenson shares twenty-three of his most representative essays, drawing on three decades of scholarship and demonstrating the consistency of the intellectual-religious interests that have animated him throughout his lifetime. These essays center on a description and examination of the complex push and pull between Jewish tradition and Western culture. Ellenson addresses gender equality, women's rights, conversion, issues relating to who is a Jew, the future of the rabbinate, Jewish day schools, and other emerging trends in American Jewish life. As an outspoken advocate for a strong Israel that is faithful to the democratic and Jewish values that informed its founders, he also writes about religious tolerance and pluralism in the Jewish state. The former president of Hebrew Union College-Jewish Institute of Religion, the primary seminary of the Reform movement, Ellenson is widely respected for his vision of advancing Jewish unity and of preparing leadership for a contemporary Judaism that balances tradition with the demands of a changing world. Scholars and students of Jewish religious thought, ethics, and modern Jewish history will welcome this erudite collection by one of today's great Jewish leaders"--